(S)-4-(2-Chloropropan-2-yl)-1-(2,2,2-trichloroethyl)cyclohexene - Brahim Boualy; Mohamed Anoir Harrad; Larbi El Firdoussi; Mustapha Ait Ali; Corrado Rizzoli (Acta Crystallographica Section E, 2011)
The title compound, C11H16Cl4, was synthesized by the reaction of (1S)-β-pinene with triethylamine in the presence of ZnCl2. The cyclohexene ring assumes a half-boat conformation. The crystal packing is governed only by van der Waals interactions. The structure, which has been refined in P21, presents a striking P21/m pseudosymmetry.